(untitled) (Web of Teachers: Inderscience Research, 2025)
In recent years, comparison syndrome has become one of the most common psychological issues among young people. This phenomenon is largely influenced by social media and modern information technologies. Constant exposure to other people’s achievements, appearances, and lifestyles often causes youth to feel inadequate, lose self-confidence, and experience anxiety or depression. This article examines the psychological effects of comparison syndrome on the mental well-being of young people, focusing on its impact on self-perception, emotional stability, and motivation. The study highlights the importance of developing healthy self-esteem and maintaining mental balance among the younger generation.